Gustatory processing and taste memory in Drosophila. (2nd April 2016) - Masek, Pavel; Keene, Alex C.
Abstract: Taste allows animals to discriminate the value and potential toxicity of food prior to ingestion. Many tastants elicit an innate attractive or avoidance response that is modifiable with nutritional state and prior experience. A powerful genetic tool kit, well-characterized gustatory system, and standardized behavioral assays make the fruit fly, Drosophila melanogaster, an excellent system for investigating taste processing and memory. Recent studies have used this system to identify the neural basis for acquired taste preference. These studies have revealed a role for dopamine-mediated plasticity of the mushroom bodies that modulate the threshold of response to appetitive tastants. The identification of neural circuitry regulating taste memory provides a system to study the genetic and physiological processes that govern plasticity within a defined memory circuit.